Navigobius asayake, a new species of ptereleotrine goby (Gobioidei: Microdesmidae) from Kagoshima, southern Japan - Okamoto, Makoto; Motomura, Hiroyuki (Zootaxa, 2018)
A new species of ptereleotrine dartfish, Navigobius asayake, is described based on four specimens (45.0–52.1 mm in standard length: SL) collected from off the Satsuma Peninsula and Tanegashima island, Kagoshima, southern Japan. It is distinguished from other congeners by the following combination of characters: second dorsal-fin rays I, 18–19; anal-fin rays I, 19; pectoral-fin rays 21–22; gill rakers 5–6 + 13–15; head length 25.1–26.4% SL; eye diameter 8.6–10.0% SL; pelvic-fin length 15.2–16.1% SL; and a well-developed yellow stripe extending from behind upper part of eye to beneath first dorsal fin.